2015
DOI: 10.1021/acs.joc.5b00604
|View full text |Cite
|
Sign up to set email alerts
|

Pt-Catalyzed Rearrangement of Oxaspirohexanes to 3-Methylenetetrahydrofurans: Scope and Mechanism

Abstract: A novel Pt-catalyzed rearrangement of oxaspirohexanes to 3-methylenetetrahydrofurans is reported. Mechanistic studies by (13)C-labeling experiments confirm oxidative addition of Pt(II) regioselectively to the least substituted carbon-carbon bond of the cyclopropane to form a platinacyclobutane intermediate. To our knowledge, this is the first alkoxy-substituted platinacyclobutane that has been observed spectroscopically. The scope and a proposed mechanism of this new Pt-catalyzed transformation are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Oxaspirohexanes that were synthesized from 2-methyleneoxetanes also underwent rearrangement catalyzed by Zeise's Pt(II) dimer. 483 Monosubstituted as well as 5,6-transdisubstituted oxaspirohexanes rearranged in good yields via a platinacyclobutane intermediate (Scheme 130). 5,6-cis-disubstituted oxaspirohexanes ring-opened to afford allyl chlorides as the major product.…”
Section: Reactivity Of 2-methyleneoxetanesmentioning
confidence: 99%
“…Oxaspirohexanes that were synthesized from 2-methyleneoxetanes also underwent rearrangement catalyzed by Zeise's Pt(II) dimer. 483 Monosubstituted as well as 5,6-transdisubstituted oxaspirohexanes rearranged in good yields via a platinacyclobutane intermediate (Scheme 130). 5,6-cis-disubstituted oxaspirohexanes ring-opened to afford allyl chlorides as the major product.…”
Section: Reactivity Of 2-methyleneoxetanesmentioning
confidence: 99%
“…<Scheme 31 near here> Spirocyclopropyl oxetanes 121 were reported to rearrange to 3-methylenetetrahydrofurans 122 upon treatment with a catalytic amount of Zeise's dimer and 20 mol% of tricyclohexylphosphine in dichloromethane at 45 °C. 102 The mechanism of this new platinum-catalyzed rearrangement was extensively studied (including with 13 C NMR-labeling) and it was found that oxidative addition of the substrate to platinum(II) was taking place at the least substituted carbon-carbon bond of the spirocyclopropyl unit. <Scheme 32 near here> Spirocyclic oxetanes 123, obtained by photocycloaddition of N-acylisatins and bicyclopropylidene, could be ring-opened by an excess of acid, such as hydrochloric or hydrobromic acid in acetonitrile at room temperature, yielding spirocyclopropyl butenolide 124 in good yield.…”
Section: Alkyne-carbonyl Metathesismentioning
confidence: 99%
“…an analogue containing S-tert-butyl (R 1 = t-Bu) rather than S-phenyl adds to other aldehydes with even greater antiselectivity ( Table 10). [85][86][87][88] Replacing O α -benzylglycolic acid S-phenyl thioester (80, R 1 = Ph, see Table 10) by O α -(tert-butyldimethylsilyl)glycolic acid S-phenyl thioester (82) as a CH acid results in Cl 3 Ti enolate formation and aldol additions that furnish the aldol adducts syn-83 with ds = 72:28 to 90:10 (Table 11). 85 Enantiomerically pure (homoisomenthyl) 2 B enolates derived from the last-mentioned S-phenyl thioester of O α -(tert-butyldimethylsilyl)glycolic acid (84, R 1 = Ph, PG = SiMe 2 t-Bu) or derived from the S-phenyl or S-tert-butyl thioester of a differently protected O α -benzylglycolic acid (84, R 1 = Ph or t-Bu, PG = Bn) undergo aldol additions with excellent asymmetric inductions and anti-selectivities (Table 12).…”
Section: Review Syn Thesismentioning
confidence: 99%